2020
DOI: 10.1007/s00394-020-02241-0
|View full text |Cite
|
Sign up to set email alerts
|

Is nutrition science ready for the twenty-first century? Moving towards transdisciplinary impacts in a changing world

Abstract: Malnutrition in an obese world was the fitting title of the 13th Federation of European Nutrition Societies (FENS) conference held in October 2019. Many individuals do not eat a healthy, well-balanced diet, and this is now understood to be a major driver of increased disease risk and illness. Moreover, both our current eating patterns and the food system as a whole are environmentally unsustainable, threatening the planetary systems we depend on for survival. As we attempt to feed a growing global population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Even results of successful RCTs performed on single components or on single foods often lead to conflicting views on what constitutes a healthy daily diet [ 150 ]. For these reasons, the principles of nutritional study designs beyond and in addition to RCTs are being evaluated and discussed in different forums.…”
Section: Assessing Health Optimisation In Non-diseased Individualsmentioning
confidence: 99%
“…Even results of successful RCTs performed on single components or on single foods often lead to conflicting views on what constitutes a healthy daily diet [ 150 ]. For these reasons, the principles of nutritional study designs beyond and in addition to RCTs are being evaluated and discussed in different forums.…”
Section: Assessing Health Optimisation In Non-diseased Individualsmentioning
confidence: 99%
“…Much of the challenge involves the redefinition of concepts of nutrition science, such as the definition of health and how to determine health status (of the individual, societal groups, nations, the planet), what to consider to be a causal effect and the process of achieving consensus based on the totality of the evidence on causality. Recently, a more detailed concept of health for the nutrition sciences was championed during a satellite workshop to the FENS conference [7,17,59]. At the same workshop, it was acknowledged that the quality of nutrition science should be at the highest level, however, taking into account that one must accept the fluidity of knowledge and that the spectrum of certainty will never be binary, either "A" or "B".…”
Section: Credibility and Capability Of Nutrition Sciences In The Persmentioning
confidence: 99%
“…Comparable initiatives in the United States [2,3], Australia [4] and elsewhere are working on increasing insights on how nutrition science can increase its credibility and capability, with each initiative taking its own approach. Discussion to date has identified that nutrition science is meeting inherent boundaries, hampering conceptual and methodological progress and the translation of novel insights into societal benefit and trust [1,5]. Nutrition science is facing limitations to its capability and credibility, impeding its societal value.…”
Section: Introductionmentioning
confidence: 99%
“…During its existence so far, the NiT discussion group has identified several main points of concern [1] that can be considered major areas for an open, honest and thorough debate and discussion, in order to catalyse a new global consensus on standards in the science of nutrition. Recently, the Federation of European Nutrition Societies (FENS) has chosen to further develop the NiT initiative and begin a more internationally oriented discussion on "Improving standards in the science of nutrition" [5]. It is now proposed to convene 3 working groups under the auspices of FENS, with each working group dealing with specific working areas: (1) the concepts and methodologies required to produce credible nutrition science in relation to public and personal health, (2) the organization, capabilities and funding structure required to produce credible nutrition science, (3) the way nutrition science is communicated to the general public and patients, to the medical community, and to industry.…”
Section: Introductionmentioning
confidence: 99%